2022
DOI: 10.3390/min12050547
|View full text |Cite
|
Sign up to set email alerts
|

Mining and Metallurgical Waste as Potential Secondary Sources of Metals—A Case Study for the West Balkan Region

Abstract: The aim of this paper is to present a chemical composition and quantities of mining and processing waste landfills material developed during historical mining and smelting. After detailed inspection, it was found that approximately 2.6 gigatons of the waste had been deposited at 1650 sites, covering almost 65 km2. More than half of this material, 55%, is characterized as conventional mining waste, 37% belongs to the processing tailings, and 8% to metallurgical waste. Most of these tailing sites are unclaimed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…It is important to emphasize that even if a residue is not directly linked to mineral exploration, it entered the subsequent analysis of this Section because its use in the composition of mineral residues in recycling processes was identified in several analyzed articles, signaling its importance. For example, metallurgical waste in [32,71,72] and steel slag in [73][74][75][76].…”
Section: Granulation With Liquid Slag Impactmentioning
confidence: 99%
“…It is important to emphasize that even if a residue is not directly linked to mineral exploration, it entered the subsequent analysis of this Section because its use in the composition of mineral residues in recycling processes was identified in several analyzed articles, signaling its importance. For example, metallurgical waste in [32,71,72] and steel slag in [73][74][75][76].…”
Section: Granulation With Liquid Slag Impactmentioning
confidence: 99%
“…According to recent studies, it has been found that approximately 2.6 gigatons of waste are deposited at 1650 sites covering almost 65 km 2 in the Western Balkans. More than half of this material, 55%, is characterized as conventional mining waste, 37% belongs to the processing tailings, and 8% to metallurgical waste [7]. The main elements for economic evaluation of the landfill are: Ag, Au, Pb, Zn, Bi, Cu, Sb, W, In, Mo, Re, while the recovery of the Kosovo tailings could bring 7310 million USD inprofit [7].…”
Section: Introductionmentioning
confidence: 99%
“…More than half of this material, 55%, is characterized as conventional mining waste, 37% belongs to the processing tailings, and 8% to metallurgical waste [7]. The main elements for economic evaluation of the landfill are: Ag, Au, Pb, Zn, Bi, Cu, Sb, W, In, Mo, Re, while the recovery of the Kosovo tailings could bring 7310 million USD inprofit [7]. More than 60 Mt of reserves from tailings have been accumulated in Kosovo.…”
Section: Introductionmentioning
confidence: 99%
“…The use of technogenic waste in the production of filling materials and/or as a potential source of minerals has recently been investigated in many countries around the world, which can be seen in published scientific papers in various journals. Some of the group authors engaged in the work and improvement of the use of waste material from the mining industry are observed in Russia [27][28][29][30][31], Czech Republic [32], Poland [33,34], China [8,11,35], Saudi Arabia [36], and Slovenia and Serbia [37]. The authors recognized the topicality of the problem created by mining waste and by using tailings, they are engaged in solving social, economic, and environmental problems.…”
Section: Introductionmentioning
confidence: 99%